„Urodziłem się pierwszy i dlatego żyję” – filmowa próba odpowiedzi na pytanie o przeznaczenie człowieka. Kilka słów o „Przypadku” Krzysztofa Kieślowskiego - Wiśniewski, Artur (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The article is an analysis and interpretation of the movie Przypadek (Blind Chance) directed by Krzysztof Kieślowski. The author suggests that this movie should be interpreted not only through the prism of the significant Polish historical events it describes (the state of the Polish society of the 70s and the 80s). The article also touches upon the political events that the movie was connected to and the artistic visions that accompanied the director during the making of the movie. The author of the article while describing every subsequent artistic device tries to build the whole interpretation of the movie.